Role of molecular signature to differentiate second primary lung cancer from metastasis in a patient with squamous cell carcinoma of oral cavity. Issue 4 (23rd June 2021) - Yilmaz, Emrullah; Gan, Gregory N.; Schroeder, Thomas M.; Cowan, Andrew; Joste, Nancy
Abstract: Background: Lung is the most common site of distant metastasis for patients with head and neck squamous cell carcinoma (HNSCC). However, differentiating second primary lung cancers from metastasis may be difficult for p16 negative HNSCC. Case: We describe a case of oral cavity squamous cell carcinoma (SCC) who was found to have lung nodule and hilar lymphadenopathy (LAD) after surgery and radiation therapy. Hilar node was consistent with SCC however, it was difficult to differentiate second primary lung cancer and metastasis from oral cavity SCC. Next‐generation sequencing was done for the primary oral cavity and the hilar node. Both samples had the same type of TP53 mutation and variants of unknown significance suggesting metastatic HNSCC. He was treated with a chemotherapy regimen for metastatic HNSCC. Conclusion: Molecular studies can help to differentiate metastasis from second primary lung cancers for p16 negative HNSCC.